Documentation and Analysis of ICT initiatives of Agricultural Research Institutions in Telangana: Application of Nudge Theory - Shilpa, Bolleboina; Jirli, Basavaprabhu (Indian Journal of Extension Education, 2023)
The present paper attempts to document various ICT initiatives of Agricultural Research Institutes in Telangana. The application of ICT offers excellent possibilities for empowering stakeholders and establishing appropriate communication between research and extension systems. A qualitative tool called nudge theory is used to identify specific nudges of various ICT initiatives. Nudge theory is a concept in the behavioral science that proposes positive reinforcement and indirect suggestions as ways to influence behavior. These are simple, low-cost interventions that alter behavior in predictable ways. A descriptive research design was adopted for the study. The nudging framework is done and classified under internally imposed, externally imposed, encouraging, discouraging, mindless and mindful factors. State Agriculture University – Electronic media wing of PJTSAU, National Academy of Agriculture Research Management, Indian Institute of Millet Research Initiatives are taken under this study and the ICT Initiatives were classified. The nudges were identified and all together overall nudging framework is done.
Keywords: Nudge theory; Initiatives; ICTs; Nudges; Telangana